Prevalence and severity of osteochondrosis of the free thoracic vertebra in three modern broiler strains and the Athens Canadian Random Bred control broiler. Issue 2 (4th March 2018) - Chen, Laura R.; Suyemoto, M. Mitsu; Sarsour, Albarra H.; Cordova, H. Alejandro; Oviedo-Rondón, Edgar O.; Barnes, H. John; Borst, Luke B.
ABSTRACT: Osteochondrosis (OCD) results from a disturbance of endochondral ossification in articular cartilage and is an important cause of lameness in several animal species, including chickens. OCD lesions in the free thoracic vertebra (FTV) of chickens are essential to the pathogenesis of pathogenic Enterococcus cecorum . The goal of this study was to determine the prevalence of OCD in the FTV among three modern broiler chicken crosses (strains A/A, A/B, and C/C) and Athens Canadian Random Bred (ACRB) chickens, which served as the control group. The effect of sex, age, strain, body weight, and incubation temperature profile on OCD severity for each group was determined. At 2, 4, 6, and 8 weeks of age, the FTV of 10 male and 10 female birds from each strain exposed to either optimal or low-early, high-late incubation temperature profiles were collected and scored histologically for OCD lesion severity. OCD spectrum lesions were detected in >70% of all strain/sex combinations, including the ACRB controls. No association was observed between mean OCD score and broiler strain, incubation temperature profile, sex, age, or body weight. These findings indicate that OCD of the FTV is common in broiler chickens with similar prevalence observed in broilers with modern genetics and the ACRB broilers which represent 1950s broiler genetics. As the parameters examined did not have a statistical correlation with OCD, additional work is needed to understand factors that contribute to development of OCD in chickens.